Corporate Governance in The Dimension of Institutional Ownership Moderates Tax Avoidance - Indriani, Etty (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2023)
Tax avoidance is a paradox between the government and corporation policies. Tax avoidance practice is a company operational activity that is a concern in corporate governance. Good corporate governance will be able to mitigate tax avoidance. The research objective to examine and provide empirical evidence on role of corporate governance structures on tax avoidance in Indonesia. Observation of data using companies that are members of the CGI Index on the Indonesia Stock Exchange in 2017-2020 with 140 observations. The results showed that among the fundamental firm characteristics that affect tax avoidance are firm profitability and leverage. Companies that have higher profits tend to increase tax avoidance. The executive character in risk taking affects tax avoidance in a negative direction. However, when institutional ownership interacts with executive characters, it will increase tax avoidance. The research finding is that the higher the proportion of institutional ownership, the higher the pressure on risk-taking executives to increase tax avoidances.